Lymphatic Drainage of Legs Reduces Edema of the Arms in Children with Lymphedema - Lívia Maria Pereira de Godoy; Paula Pereira de Godoy Capeletto; Maria de Fátima Guerreiro Godoy; Jose Maria Pereira de Godoy (Hindawi Limited, 2018)
Objective. The aim of the present study is to report on the reduction of edema of lymphedematous arms just by treating the lower limbs. Methods. A 16-year-old girl reported that she has started having right lower limb edema at the age of three. At age 13, she performed a lymphoscintigraphy that confirmed the diagnosis of primary lymphedema of the four limbs. Recently she sought treatment at the Clínica Godoy in São Jose do Rio Preto where she was submitted to intensive treatment for eight hours per day for five days using manual (Godoy & Godoy technique) and mechanical lymphatic therapy (RA Godoy®) of the lower limbs, cervical lymphatic therapy (cervical stimulation), and the continuous use of a grosgrain stocking. Results. At the end of treatment, reductions in the sizes of both arms and legs were noted even without the use of any specific therapy for the arms. After four years, the size of the arms was normal. Conclusion. Treatment of lymphedema of the legs has systemic repercussions that may lead to the reduction in swelling of other untreated regions of the body.